Faculty Qualification as Predictor of Faculty Performance of Two State Universities in Mindanao, Philippines - Salvador, Ruel S. (JPAIR Institutional Research, 2016)
Competent faculty members in an institution play a vital role in attaining success to students, giving them the best training and education. The study aimed to review the faculty profile of the faculty members in the satellite campuses of the Mindanao University of Science and Technology (MUST) and the Jose Rizal Memorial State Universities (JRMSU) as of 2015. A descriptive survey method with a purposive sampling technique was employed. The data were collected from 90 respondents from the satellite campuses of which 14 came from MUST and 76 from JRMSU, Philippines. Researcher-made questionnaires were distributed to the faculty members. The results reveal that both institutions are female-dominated and that majority of the respondents are married. Most of them have obtained teaching experience for more than five years in teaching, 40 years old and above on the average. Research and extension works culture were not given priority among the faculty members. Majority of the satellite faculty members do not possess academic qualifications in teaching. The study suggested ways to improve the faculty profile by providing adequate support and assistance and to ensure that their existing faculty members in the satellite campuses become competitive at par with the leading universities in the Philippines and abroad.
Keywords: Higher Education; Faculty Profile; Educational Qualification; Descriptive Research; Philippines